Beyond Identity Boundaries: Interethnic and Interfaith Marriages in Indonesia - Nurul Husna; Andi Farahdhiba Irfan; Risatul Kautsari (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Drawing exclusively on secondary data from publicly available national surveys and institutional reports, including the Indonesia Demographic and Health Surveys (IDHS), which cover approximately 50,000 scientifically selected households across all provinces, this study analyzes national patterns of interethnic and interfaith marriages and their broader social implications. Data from the Central Bureau of Statistics show that interethnic marriages account for 89.3 percent of marriages, while data from the Indonesian Conference on Religion and Peace (ICRP) indicate a monthly increase of 12–15 interfaith marriage cases. These findings demonstrate a consistent growth of interethnic and interfaith marriages across regions, with Java and Bali showing particularly notable increases, especially among Muslim–Christian–Catholic unions. The rise in interethnic marriages is closely associated with urbanization, higher educational attainment, and intensified cross-ethnic interaction, while the growth of interfaith marriages reflects expanding religious diversity and shifting social norms. This study argues that interethnic and interfaith marriages function as a form of social integration that challenges rigid identity boundaries and reinforces Indonesian nationalism grounded in diversity. From a socio-legal and human rights perspective, the findings highlight the urgency of systematic state recognition and registration of interfaith marriages to ensure equal legal protection and to prevent institutional discrimination against citizens.